Association Between Childhood Maltreatment and Symptoms of Obsessive-Compulsive Disorder: A Meta-Analysis - Ou, Wenwen; Li, Zhijun; Zheng, Qi; Chen, Wentao; Liu, Jin; Liu, Bangshan; Zhang, Yan (Frontiers in Psychiatry, 2021)
Background: Previous studies have indicated that childhood maltreatment (CM) may potentially influence the clinical symptomatology of obsessive-compulsive disorder (OCD). Here, we aimed to quantify the relationship between CM and obsessive-compulsive symptoms (OCS) and depressive symptoms in OCD through a meta-analysis. Method: We searched PubMed, Embase, Cochrane Library, and PsycARTICLES databases for articles reporting the association between CM and OCD on April 15, 2020. Random-effect models were used to quantify the relationship between CM and the severity of OCS and depressive symptoms in OCD. Results: Ten records with 1611 OCD patients were included in the meta-analysis. The results revealed that CM is positively correlated with the severity of OCS (r=0.10, 95%Confidence Interval(CI): 0.01-0.19, P=0.04) as well as depressive symptoms in OCD (r=0.15, 95%CI: 0.07-0.24, P=0.0002). For the subtypes of CM, childhood emotional abuse(CEA) and childhood sexual abuse(CSA) was related with the severity of OCS (r=0.11, 95%CI: 0.03-0.19, P=0.009) and obsession (r=0.13, 95%CI: 0.03-0.23, P=0.01),respectively. Conclusion: Our meta-analysis indicates that OCD patients who suffered more CM may exhibit more severe OCS and depressive symptoms.